2023
DOI: 10.1108/cms-01-2022-0008
|View full text |Cite
|
Sign up to set email alerts
|

Freedom or bondage? The double-edged sword effect of work connectivity behavior after-hours on employee occupational mental health

Abstract: Purpose This study aims to explore the double-edged sword effect of work connectivity behavior after-hours (WCBA) on employees’ occupational mental health. Drawing on job demand-resource theory, the authors examined the double mediating mechanism of work autonomy and work-family conflict on the relationship of WCBA, work engagement and work burnout. At the same time, the authors examined the moderating role of responsiveness from superiors, hoping to clarify how WCBA brings employees positive experiences (enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Schaufeli et al (2002) [32] defined work engagement as a positive, fulfilling, work-related psychological state characterized by vigor, dedication, and absorption. Consistent with the argument of the JD-R model, numerous studies have demonstrated that working environment and work forms are important factors influencing the work-related psychological states of employees [33], and different work forms can influence the level of work engagement by altering job demands and resources for employees [34,35]. Therefore, we posit that remote work will alter the impact of work connectivity behavior after-hours on employees' work engagement.…”
Section: Work Connectivity Behavior After-hours and Work Engagementsupporting
confidence: 64%
See 1 more Smart Citation
“…Schaufeli et al (2002) [32] defined work engagement as a positive, fulfilling, work-related psychological state characterized by vigor, dedication, and absorption. Consistent with the argument of the JD-R model, numerous studies have demonstrated that working environment and work forms are important factors influencing the work-related psychological states of employees [33], and different work forms can influence the level of work engagement by altering job demands and resources for employees [34,35]. Therefore, we posit that remote work will alter the impact of work connectivity behavior after-hours on employees' work engagement.…”
Section: Work Connectivity Behavior After-hours and Work Engagementsupporting
confidence: 64%
“…Employees can attain more positive psychological states at work in conditions with work autonomy, such as having a strong sense of responsibility [37], enhancing their perceived self-effectiveness, creativity, and proactivity [39,40]. Previous studies have shown that employees perceive greater work autonomy in non-fixed and flexible work arrangements [35,41]. The study conducted by Cavazotte et al (2014) [10] demonstrated that work connectivity behavior after-hours breaks the boundaries of work time and space, and enhances the freedom and capacity for self-decision in employees' work.…”
Section: The Mediating Role Of Work Autonomymentioning
confidence: 99%
“…When workers interpret HRM signals as silent and distinctive, they are inclined to view the HRM system as strategically relevant to their job goals and therefore dedicate great effort and enthusiasm for goal attainment (Ostroff and Bowen, 2016). These positive mindsets are likely to help employees tackle job stress and burnout (Frenkel et al , 2012; Zhu et al , 2023). However, it is possible for workers to perceive that they must perform more tasks when the HRM messages are silent and highly relevant to their daily jobs.…”
Section: Discussionmentioning
confidence: 99%